Electronic Stethoscope Equipped with IoT-based Remote Monitoring to Detect Disease Symptoms - Hamzah, Torib; Setioningsih, Endang Dian; Sumber, Sumber; Ragimova, Nazila (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2022)
Auscultation is a technique or method most often used by medical personnel in the initial examination of patients. One way to carry out this method is by using a stethoscope. However, this method has its drawbacks because the diagnosis is carried out subjectively and cannot be relied on with the accuracy to diagnose the symptoms of heart defects. Thus, the purpose of this study was to create an IoT system for electronic stethoscopes with BPM value output and make analog filters to eliminate noise interference which was a major obstacle in previous studies. The contribution of this research is to make it easier for medical users to analyze heart rate using an electronic stethoscope while at the same time being able to know the number of BPM automatically that can be monitored remotely because it used IoT system. Furthermore, the method used in this study was by using a mic condenser placed on the patient's chest to detect pressure changes. When the pressure changes, the voltage output value on the condenser mic also changes. In this case, the output from the condenser mic went in and follows the analog signal conditioning circuit. The output signal from the analog signal conditioning further entered the programmed microcontroller. Furthermore, based on the measurement conducted, the error value of BPM was obtained from the five respondents. In this case, the error value generated from respondent 1 was 0.33 BPM, the error value obtained from respondent 2 was 0.67 BPM, the error value obtained from respondent 3 was 0.5 BPM, the error value obtained from respondent 4 was 0.67, and the error value obtained from respondent 5 was 0.67 BPM. Meanwhile, the results of the statistical test obtained P-Value of more than 0.05, indicating that the resulting value did not have a significant difference.